2018
DOI: 10.1080/02701367.2018.1446069
|View full text |Cite
|
Sign up to set email alerts
|

One Teacher’s Experience of Teaching Physical Education and Another School Subject: An Inter-Role Conflict?

Abstract: The study results suggest that the already complex and multifaceted role of a school teacher (Richards, Templin, Levesque-Bristol, & Blankenship, 2014) seems to be further complicated when teachers are tasked with simultaneously teaching physical education and another school subject. With the presence of a role conflict management strategy such as role prioritization (Stryker, 1968), one can presume that teachers who are tasked with teaching physical education and another school subject may experience some lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 27 publications
0
15
0
1
Order By: Relevance
“…While a significant amount of work has been done on the teacher-coach conflict (see Konukman et al, 2010), only one qualitative study (see Iannucci and MacPhail, 2018) has begun to identify and understand the dual role conflict experienced by teachers of multiple subjects, specifically PE and another school subject(s). In a study conducted by Iannucci and MacPhail (2017) it was suggested that when teachers are responsible for teaching multiple school subjects they can experience a push-pull dynamic between the two roles.…”
Section: Teaching Multiple School Subjects Role Conflictmentioning
confidence: 99%
See 4 more Smart Citations
“…While a significant amount of work has been done on the teacher-coach conflict (see Konukman et al, 2010), only one qualitative study (see Iannucci and MacPhail, 2018) has begun to identify and understand the dual role conflict experienced by teachers of multiple subjects, specifically PE and another school subject(s). In a study conducted by Iannucci and MacPhail (2017) it was suggested that when teachers are responsible for teaching multiple school subjects they can experience a push-pull dynamic between the two roles.…”
Section: Teaching Multiple School Subjects Role Conflictmentioning
confidence: 99%
“…However, it was also proposed that teaching a combination of two subjects may dilute the negative effects of challenges faced by teachers of a marginalized school subject when responsible for teaching that subject for the entirety of their allocated teaching hours. Revisiting the data through a role theory lens, Iannucci and MacPhail (2018) identified parallels between one participant's professional life and the teacher-coach conflict literature. The results of their study suggest that dual subject teachers can, and perhaps do, experience role conflict.…”
Section: Teaching Multiple School Subjects Role Conflictmentioning
confidence: 99%
See 3 more Smart Citations